2015
DOI: 10.1589/jpts.27.3255
|View full text |Cite
|
Sign up to set email alerts
|

The effect of physician experience on the measurement reliability of the Reimers’ hip migration percentage in children with cerebral palsy

Abstract: [Purpose] Reimers’ hip migration percentage (MP) is commonly used to document the extent of hip displacement in children with cerebral palsy (CP). However, factors such as poor administration of pelvic radiographs, a lack of concentration, inexperience, or a busy clinical environment may result in variations in the MP measurements. The aim of this study was to compare the differences in the MP results of two physiatrists with varying levels of experience to determine the role of experience in the measurement’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Another analysis compared the reliability of the MP between an experienced and inexperienced physiotherapist and found excellent ICC of 0.94. 30 Our findings support the use of digital templating software as the ICC between the four observers in this study ranged between 0.939 and 0.993 for the CM and 0.894 and 0.993 for the MM.…”
Section: Discussionsupporting
confidence: 86%
“…Another analysis compared the reliability of the MP between an experienced and inexperienced physiotherapist and found excellent ICC of 0.94. 30 Our findings support the use of digital templating software as the ICC between the four observers in this study ranged between 0.939 and 0.993 for the CM and 0.894 and 0.993 for the MM.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the results of MP were divided into three stages according to a general criterion for classifying the MP; MP < 33% is considered to be insignificant in hip dislocation, MP 33%–40% requires intensified observation, and MP > 40% requires surgical intervention. [ 28 , 29 ] In this study, as the severity of MP increased, the proportion of HH increased in pediatric CP patients. In addition, a statistically significant difference was found when comparing the MP levels of patients without and with HH.…”
Section: Discussionmentioning
confidence: 61%
“… 15 Using manual measurement with physical radiographs, pens and goniometers, the standard error of measurement × 1.96 for experienced raters is 5.8% for one rater and 11% between raters, 12 and the 95% CI for orthopaedic trainees is 12.9% for one rater and 22% between raters. 16 Using digital measurement tools on a digital PACS system, Analan et al 17 found that an experienced physiatrist and a physiatry resident had high inter-rater correlations of 0.94 at each of two measurement sessions. Though Cliff et al 11 did not discuss the method of measurement, their study established that when experienced radiologists measure MP in standardized radiographs obtained using a positioning protocol, the mean absolute difference in MP was 3.2% ( sd 3.5%) for a single rater and 3.7% ( sd 3.8%) for multiple raters.…”
Section: Discussionmentioning
confidence: 99%